2019
DOI: 10.1055/s-0039-1678585
|View full text |Cite
|
Sign up to set email alerts
|

A Multifactor Approach to Mild Cognitive Impairment

Abstract: Mild cognitive impairment (MCI) represents an intermediate stage between normal cognition and dementia. Individuals with MCI are at increased risk of conversion to dementia, and the rate of progression of MCI to dementia is dependent on age, gender, and education. MCI may be diagnosed using neuropsychological criteria using cut-offs representing decrements in cognition, or using criteria to assess for a decline in functional status. The ability to determine the status of dementia-related biomarkers has allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In many longitudinal studies, the conversion rate was reported from the overall follow‐up period and then the ACR was calculated to estimate the progression of MCI in 1 year, but our study reported only 1‐year rate of conversion. Because some MCI patients may revert to normal especially during the 1 year after diagnosis, 30 and the rate of conversion may progress over time, the average ACR may be the better marker to represent the overall MCI prediction.…”
Section: Discussionmentioning
confidence: 99%
“…In many longitudinal studies, the conversion rate was reported from the overall follow‐up period and then the ACR was calculated to estimate the progression of MCI in 1 year, but our study reported only 1‐year rate of conversion. Because some MCI patients may revert to normal especially during the 1 year after diagnosis, 30 and the rate of conversion may progress over time, the average ACR may be the better marker to represent the overall MCI prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the neuropsychological classification of MCI and AD has been enriched by the employment of new methodologies since cognition is not the only area affected by dementia. So far, there has been a lack of emphasis on non-cognitive symptoms in MCI and early dementia, whereas behavioral and motor issues are prevalent [Qarni & Salardini (2019)].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, clinical research and basic research have focused on the preclinical stage of dementia-mild cognitive impairment (MCI) (1). MCI denotes problems with memory, attention, or other cognition, which are greater than expected for healthy aging but insufficient to interfere with daily activities (2). The clinical outcomes of MCI may remain stable, progress to dementia, or return to neurological integrity.…”
Section: Introductionmentioning
confidence: 99%